Sustainable Supply Chain Management and Its Impact On Corporate Performance - Ahmed Al-Mahdi; Omar Rahman; Layla Karim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This paper investigates the impact of sustainable supply chain management (SSCM) practices on corporate performance. Focusing on multinational corporations, the study assesses the effectiveness of green sourcing, waste reduction, and ethical labor practices in enhancing operational efficiency and reputation. Findings suggest that adopting SSCM practices not only improves environmental outcomes but also leads to increased profitability and customer loyalty.